The surface area of a square pyramid can be calculated using the equation S=12lp+B

. Rearrange the surface area equation for the quantity of interest B
.(1 point)
B=

1 answer

To rearrange the surface area equation for the quantity of interest \( B \), we start with the original equation:

\[ S = \frac{1}{2} l p + B \]

where:

  • \( S \) is the surface area of the pyramid,
  • \( l \) is the length of the base,
  • \( p \) is the slant height,
  • \( B \) is the area of the base.

To isolate \( B \), we will subtract the term \( \frac{1}{2} l p \) from both sides of the equation:

\[ B = S - \frac{1}{2} l p \]

So, the rearranged equation for \( B \) is:

\[ B = S - \frac{1}{2} l p \]